1989
DOI: 10.1136/adc.64.10_spec_no.1388
|View full text |Cite
|
Sign up to set email alerts
|

Ciprofloxacin in neonatal Enterobacter cloacae septicaemia.

Abstract: rupture and dissection has been described and was the probable cause of death in five of the 51

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 6 publications
1
18
0
Order By: Relevance
“…Available knowledge on cipro¯oxacin therapy in very low birth weight (<1500 g) infants with neonatal infections (onset of infection before postconceptional age of 40 weeks) [1,5,7] comprises reports on 27 newborns. The infants gestational ages ranged from 24 to 37 weeks (mean 31 weeks), postnatal ages at the time of ciprooxacin therapy from 4 to 137 days (mean 28 days) and body weights from 800 to >2100 g (mean 1230 g).…”
Section: Analysis Of Reported Casesmentioning
confidence: 99%
See 2 more Smart Citations
“…Available knowledge on cipro¯oxacin therapy in very low birth weight (<1500 g) infants with neonatal infections (onset of infection before postconceptional age of 40 weeks) [1,5,7] comprises reports on 27 newborns. The infants gestational ages ranged from 24 to 37 weeks (mean 31 weeks), postnatal ages at the time of ciprooxacin therapy from 4 to 137 days (mean 28 days) and body weights from 800 to >2100 g (mean 1230 g).…”
Section: Analysis Of Reported Casesmentioning
confidence: 99%
“…Most of these patients were over 6 years of age and reports on the use of cipro¯oxacin in neonates are limited [1,3,5,7]. We report the use of cipro¯oxacin in a preterm infant with an invasive infection due to a multiresistant Enterobacter cloacae and review the available cipro¯oxacin information in preterm neonates.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The patient was followed up to the age of 36 months and neurological fits, dental dyschromia and signs of arthorapthy were not observed. In another report, six premature infants who had had multi-resistant E. cloacae infection and were treated with ciprofloxacin did not show any side effects [9]. Isaac et al [10] reported the successful treatment of ventriculitis caused by a multi-resistant P. aeruginosa strain.…”
Section: Discussionmentioning
confidence: 99%
“…In the published cases, patients have received up to 60 mg/kg per day of ciprofloxacin for up to 30 days [5,8,10]. Van den Oever et al [11] suggested, however, that an intravenous dose of 10-20 mg/kg per day is probably adequate for pre-term infants, as adequate peak serum levels (0.98-5.7 mg/l) are still demonstrated, even at relatively low doses (4-10 mg/kg per day) [1,5]. Indeed, adequate ciprofloxacin CSF penetration for meningitis has been established both in adults and infants of all ages (reaching about 65%-150% of serum levels) [4,11].…”
mentioning
confidence: 96%